Impact of metabolic syndrome on lower urinary tract symptoms in patients with benign prostate hyperplasia (Faculty of Medicine Universitas Indonesia, 2021)
BACKGROUND Studies evaluating the relationship between metabolic syndrome (MetS) and lower urinary tract symptoms (LUTS) in men with benign prostate hyperplasia (BPH) are lacking in Indonesia. This study aimed to discover the association of LUTS and MetS in men with BPH. METHODS Subjects who underwent biopsy were recruited from Cipto Mangunkusumo Hospital, Jakarta, Indonesia from January 2014 to January 2018, but only men who had biopsy-proven BPH were included. Body mass index, waist circumference, fasting blood glucose, triglyceride, high-density lipoprotein, prostate volume (PV), and international prostate symptom score (IPSS) were collected before the biopsy. MetS criteria were based on the National Cholesterol Education Program Adult Treatment Panel III. IPSS was assessed for LUTS and consisted of irritative and obstructive symptoms and quality of life (QoL). Independent t-test or Mann–Whitney test was used to analyze numerical data. RESULTS Of 227 men with biopsy-proven BPH, 87 (38.3%) were diagnosed with MetS. PV was similar in men with or without MetS (54.4 [20.3–100] versus 49.9 [19.5–100] cm3, p = 0.239). Men with MetS generally had more LUTS (15 [1–30] versus 11 [0–35], p = 0.005), more irritative symptoms (8 [0–20] versus 6 [0–20], p = 0.007), and lower QoL (4 [0–6] versus 3 [0–6], p = 0.018). CONCLUSIONS BPH patients with MetS had greater LUTS, particularly irritative symptoms and QoL score.